Nazi policy towards the Lithuanian lndustry and its results - Braslauskas, Justinas (Lietuvos istorijos studijos, 2003)
The industrial organization during the period of Nazi occupation was influenced mainly by an external factor, Germany, and not by an internal development of the economy. Germany was an aggressor state whose objective was to gradually integrate the local economy into its own structure. Only those industrial enterprises which could find local raw materials and could offer products important for the occupants managed to continue their business operations during the years of German occupation. Other industrial enterprises were closed by the occupant authorities. Many private companies were closed by their owners or were on the verge of bankruptcy. The decrease in the number of industrial enterprises was one of the main causes of a rapid decline in this sphere of the economy. During the years of Nazi occupation, industrial workers lived under severe social conditions. Their salaries were extremely low; in most cases, they did not even earn a living wage. Due to difficult living conditions, expensive low-quality health care, and the spread of various diseases, the mortality rate among factory workers and office employees was on a constant increase. On the other hand, it is true that the Nazis, during the period of occupation, put much effort into industrial specialist training programs. This policy was part of their plan to annex Lithuania after the end of World War II. Besides, a bigger part of the Jewish population had already been exterminated, among them many outstanding specialists in this branch of the industry.